Diversity of auger beetles (Coleoptera: Bostrichidae) in the mid-cretaceous forests with description of seven new species - Legalov, Andrei A. (Diversity)
The diversity and abundance of auger beetles were compared with ecologically similar families of other beetles. It was shown that the ecological niche in dead wood, which in the Paleogene belonged to bark and ambrosia beetles, was occupied by Bostrichidae in the Mesozoic. Seven new species, Poinarinius aristovi sp. nov., P. antonkozlovi sp. nov., P. lesnei sp. nov., P. perkovskyi sp. nov., P. zahradniki sp. nov., P. borowskii sp. nov., and P. cretaceus sp. nov. from the subfamily Alitrepaninae of the family Bostrichidae are described from mid-Cretaceous Burmese amber. The key to the species of the genus Poinarinius Legalov, 2018 is given. The new synonym, Alitrepanum Peng, Jiang, Engel & Wang, 2022, syn. nov. to Poinarinius, was established. A list of the fossil Bostrichidae was compiled.